Apprenticeship in Lebanon - Abourjeili, Nicolas [Verfasser] (My University, 2012)
"The focus of this article is Lebanon's vocational and technical education (VTE) system, and in particular, recent efforts to enhance its performance. The article discusses the development of the Lebanese VTE system and provides an overview of the challenges it faces. Lebanon's work with Germany, in terms of reforming Lebanon's apprenticeship system, is a primary focus." (Authors' abstract, BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; I 1.1 Systemberatung; I 2.3.4 Asien; Berufsbildungssystem; Duales System; Transfer; Bildungsreform; Libanon